Highly Selective Optical Sensor Eu (TTA)3 Phen Embedded in Poly Methylmethacrylate for Assessment of Total Prostate Specific Antigen Tumor Marker in Male Serum Suffering Prostate Diseases - Garoub, Mohannad; Hefny, A. H.; Omer, W. E.; Elsaady, Mostafa M.; Abo-Aly, Mohamed M.; Sayqal, Ali A.; Alharbi, Ahmed; Hameed, Ahmed; Alessa, Hussain; Youssef, A. O.; Mohamed, Ekram H.; Gouda, Ayman A.; et al. (Frontiers in Chemistry, 2020)
A low-cost, simple, and highly selective method was used for the assessment of total prostate-specific antigen (tPSA) in serum samples of males with prostate cancer. This method depends on the quenching of the luminescence intensity of the optical sensor Eu (TTA)3 phen embedded in poly methylmethacrylate (PMMA) thin film by different concentrations of tPSA. The luminescent optical sensor was synthesized and characterized through absorption, emission, X-ray diffraction (XRD), and scanning electron microscopy (SEM), and is tailored to present red luminescence at 614 nm upon excitation at 395 nm in water. The performance of the designed sensor is based on the quenching of the fluorescence intensity by tPSA in water. The sensing mechanism was based on the fluorescence resonance energy transfer (FRET). This quenching was successfully utilized for the determination of tPSA in serum samples from prostate cancer patients with a detection limit of about 0.0469 ng mL-1 and a correlation coefficient of 0.99. The method was used satisfactorily for the assessment of tPSA concentration in serum samples of patients with prostate disease in the in time and cost effective way.